Morbidity during the first year of life in small for gestational age infants. Issue 1 (July 1996) - Vik, T; Vatten, L; Markestad, T; Ahlsten, G; Jacobsen, G; Bakketeig, L S
Abstract : Postneonatal morbidity during infancy was studied in 284 small for gestational age (SGA) and 359 non-SGA term infants. None of these babies had congenital malformations and they were born to para 1 and para 2 mothers. SGA infants had an increased risk (OR: 1.7, 95% confidence interval: 1.1-2.6) of being admitted to hospital compared with non-SGA infants. The principal cause was respiratory tract infections. Increased hospitalisation among SGA infants was a factor only if the mother was a smoker-that is, smoked cigarettes at the time of conception. Among subgroups of SGA babies, there was an increased risk for infants of non-repeaters (women without a previous SGA child) (OR: 2.4, 95% CI: 1.4-3.8) and for infants with symmetric (OR: 2.0, 95% CI: 1.2-3.3) body proportions compared with non-SGA infants. The results suggest that, beginning in early pregnancy, growth retardation may have long term consequences for subsequent infant morbidity, particularly if the mother is smoker.